New species and records of black flies (Diptera: Simuliidae) from Vinh Phuc Province, Vietnam - Takaoka, Hiroyuki; Sofian-Azirun, Mohd; Ya’cob, Zubaidah; Chen, Chee Dhang; Lau, Koon Weng; Pham, Hong Thai (Zootaxa, 2014)
Four new species of black flies are described, and three others are reported as newly recorded, based on adults reared from pupae, pupae and larvae collected in and near Tam Dao National Park, Vinh Phuc Province, Vietnam. New species include Simulium (Gomphostilbia) hongthaii sp. nov., S. (G.) tamdaoense sp. nov. (both species placed in the asakoae species-group), S. (Simulium) taythienense sp. nov. and S. (S.) xuandai sp. nov. (the two latter species placed in the striatum species-group). Newly recorded species are S. (G.) brinchangense Takaoka, Sofian-Azirun & Hashim, S. (Nevermannia) aureohirtum Brunetti and S. (S.) brevipar Takaoka & Davies. These discoveries increase the number of species of black flies known in Vietnam from 21 to 28.